Analisis Big Data dalam Peminatan Mahasiswa Baru: Pendekatan Ekologis untuk Inovasi Pembelajaran Bahasa - Fitriyatul Qomariyah; Zainatul Mufarrikoh (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The study of new student interest in the Tarbiyah Faculty of IAIN Madura reflects prospective students' preferences for various study programs, which are essential to design adaptively in response to social changes and global challenges, including environmental issues. This research focuses on analyzing student interest using big data to understand trends in program selection and its relevance to ecological education in language learning. The research employs a quantitative approach with secondary data analysis, utilizing Python programming and libraries such as Pandas and Matplotlib for data processing and visualization from 2014 to 2020. The analysis reveals that the Islamic Education Management (MPI) and Islamic Counseling Guidance (BKPI) programs have the highest levels of interest, while the Arabic Language Education (PBA) program is less favored. Most prospective students come from the Madura region with backgrounds in general education and pesantren. Based on these findings, this study recommends the integration of ecological education into popular programs’ curricula to enhance environmental awareness among students. These findings are expected to assist the Tarbiyah Faculty in designing a curriculum that is more responsive to community needs and environmental challenges, while supporting student character development based on ecological and Islamic values.